A P/N-containing hardener endowing bio-based epoxy thermosets with excellent thermal, mechanical and intrinsically flame-retardant performances. (10th April 2023) - Guo, Wenwen; Liang, Fuwei; Chen, Shun; Jin, Liping; Ji, Chenpeng; Zhang, Ping; Fei, Bin
Highlights: An intrinsically flame-retardant bio-based epoxy thermoset was synthesized. It exhibited comparable Tg, mechanical modulus and strength with DGEBA. It achieved a LOI of 33.5% and UL-94 V-0 rating. It exhibited significantly decreased PHRR and THR as compared to neat sample. It presented notably reduced pyrolysis volatiles in comparison with neat sample. Abstract: In view of the drawbacks of severe dependence on petroleum resources and flammability of commercial epoxy thermosets, a novel intrinsically flame-retardant bio-based epoxy resin was manufactured through the curing reaction between the synthesized cardanol-derived epoxy monomer (CFEP) and a DOPO-based curing agent (DPDM). In addition, CFEP and DGEBA thermosets cured by DDM were used as the contrast samples. The TGA results showed that CFEP-DPDM possessed significantly enhanced thermal stability with higher char residues of 10.3 % and 17.8 % at 700 °C for air and N2 atmospheres, respectively, which were higher than those of both DGEBA-DDM (0.76 % and 12.4 %) and CFEP-DDM (3.4 % and 12.2 %). The Tg of CFEP-DPDM was 162.0 ℃ which was obviously higher than that of neat CFEP-DDM (95.2 ℃) and comparable to that of commercial DGEBA-DDM (154.1 ℃) under DMA test, and DSC test presented similar trend of Tg results. Moreover, CFEP-DPDM possessed the highest crosslinking density (νe ), indicating excellent mechanical property, which was further verified by tensile analysis that the tensile strength (44.6 MPa) and tensile modulus (3.2 GPa) of CFEP-DPDM was comparable to commercial DGEBA-DDM. As for the fire-retardant performance, CFEP thermoset cured with DPDM exhibited a high LOI value of 33.5 % and passed UL-94 V0 rating. Furthermore, compared to those of CFEP-DDM, the PHRR, THR, CO2 P and FIGRA of CFEP-DPDM were declined by 41.0 %, 37.6 %, 60.0 % and 39.8 %, respectively. Ultimately, the flame-retardant mechanism of CFEP-DPDM was investigated by further condensed and gas phases analyses. In brief, the synthesized bio-based epoxy thermosets with excellent comprehensive performance displaying high promise for application.